ALIH KODE (CODE SWITCHING) DAN CAMPUR KODE (CODE MIXING) DALAM KEGIATAN BELAJAR MENGAJAR DI KELAS X MA AN-NAWAWI SARWODADI - Akmalia; Eko Prasetyo (STKIP Subang, 2025)
This research aims to examine the phenomenon of code-switching and code-mixing in learning interactions in class X of MA An-Nawawi Sarwodadi, Wonosobo. The background of a homogeneous community with Javanese as their native language encourages this linguistic dynamic in the school environment. The research method used was descriptive qualitative with data collection techniques through passive participant observation and unstructured interviews. The results showed that code-switching and code-mixing appeared in various forms, such as switching from Indonesian to Javanese in full and inserting Javanese words/phrases into Indonesian. This phenomenon does not occur randomly; instead, it functions as an effective communication strategy to facilitate the understanding of instructions, create familiarity, build emotional closeness between teachers and students, and create a more relaxed learning atmosphere. The conclusion of this research underlines that code-switching and code-mixing are forms of teachers' pedagogical skills and contextual language dynamics, which actually enhance learning effectiveness while preserving local wisdom values.